Overexpression of Key Sterol Pathway Enzymes in Two Model Marine Diatoms Alters Sterol Profiles in Phaeodactylum tricornutum - Ana Cristina Jaramillo-Madrid; Raffaela Abbriano; Justin Ashworth; Michele Fabris; Mathieu Pernice; Peter J. Ralph (MDPI AG, 2020)
Sterols are a class of triterpenoid molecules with diverse functional roles in eukaryotic cells, including intracellular signaling and regulation of cell membrane fluidity. Diatoms are a dominant eukaryotic phytoplankton group that produce a wide diversity of sterol compounds. The enzymes 3-hydroxy-3-methyl glutaryl CoA reductase (HMGR) and squalene epoxidase (SQE) have been reported to be rate-limiting steps in sterol biosynthesis in other model eukaryotes; however, the extent to which these enzymes regulate triterpenoid production in diatoms is not known. To probe the role of these two metabolic nodes in the regulation of sterol metabolic flux in diatoms, we independently over-expressed two versions of the native HMGR and a conventional, heterologous SQE gene in the diatoms Thalassiosira pseudonana and Phaeodactylum tricornutum. Overexpression of these key enzymes resulted in significant differential accumulation of downstream sterol pathway intermediates in P. tricornutum. HMGR-mVenus overexpression resulted in the accumulation of squalene, cycloartenol, and obtusifoliol, while cycloartenol and obtusifoliol accumulated in response to heterologous NoSQE-mVenus overexpression. In addition, accumulation of the end-point sterol 24-methylenecholesta-5,24(24')-dien-3β-ol was observed in all P. tricornutum overexpression lines, and campesterol increased three-fold in P. tricornutum lines expressing NoSQE-mVenus. Minor differences in end-point sterol composition were also found in T. pseudonana, but no accumulation of sterol pathway intermediates was observed. Despite the successful manipulation of pathway intermediates and individual sterols in P. tricornutum, total sterol levels did not change significantly in transformed lines, suggesting the existence of tight pathway regulation to maintain total sterol content.